2011
DOI: 10.1111/j.1470-6431.2011.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Teacher perceptions of the contribution of Home Economics to sustainable development education: a cross‐cultural view

Abstract: This paper reports on the contribution of Home Economics to sustainable development education as part of the school curriculum for students aged 11–18 years in a number of cultural contexts. A survey was used to collect data from Home Economics teachers in Australia, Canada, Malta and Scotland to better understand the similarities and differences of Home Economics curriculum in these contexts, as it contributes to sustainable development education. The data reveal that the teachers in the study considered sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 8 publications
0
21
0
3
Order By: Relevance
“…A previous study with Finnish HE teachers has shown that the dominant facilitating factor for implementing SD in teaching was their interest and enthusiasm [32]. Accordingly, and as reported by Dewhurst and Pendergast [29], not being regarded as a subject contributing to SD education is an inhibiting factor that negatively affects the capacity of HE teachers to engage pupils in activities aligned with educational and, in turn, social goals related to sustainable development in general, and education for sustainable food consumption in particular.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A previous study with Finnish HE teachers has shown that the dominant facilitating factor for implementing SD in teaching was their interest and enthusiasm [32]. Accordingly, and as reported by Dewhurst and Pendergast [29], not being regarded as a subject contributing to SD education is an inhibiting factor that negatively affects the capacity of HE teachers to engage pupils in activities aligned with educational and, in turn, social goals related to sustainable development in general, and education for sustainable food consumption in particular.…”
Section: Discussionmentioning
confidence: 83%
“…By identifying possible influencing factors surrounding a subject (such as perceived needs and challenging circumstances), opportunities for long-term quality progression throughout tailored resource development will increase [51], and HE teachers have a significant role to play in providing such identifications [28,29,32]. The present paper is a part of a wider project exploring the implementation and implications of incorporating a SD perspective in Swedish HE mission with an intention of generating a pertinent hypotheses and propositions for further inquiries.…”
Section: Introductionmentioning
confidence: 99%
“…The large emphasis on prescribing what is “right” or “wrong”, on fostering, and on what might even be described as paternalism is not unexpected, based on the history of HE in Sweden and internationally (Alex, ; Smith & de Zwart, ; Ma & Pendergast, ; Brembeck, ) or on contemporary research (Höijer et al ., ; Höijer, ). International surveys also show that HE education is often discussed and defined in terms of needs (Turkki, ; Dewhurst & Pendergast, ) despite the objections raised in consumer culture theory (Slater, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hjälmeskog () recently argued for HCS teaching to take a more active stance on promoting sustainability. Slater (, p. 623) suggested implementation of food literacy programs “ advocating for […] changes that enhance nutritional health” (emphasis added), and Dewhurst and Pendergast (, p. 576) point to the future of HE as a force for “changing lifestyles.” All these researchers emphasise promoting an actual change in food consumption rather than just informing students about consequences. Turning to needs, Turkki (, p. 279) describes the main benefit of HE as being able to “link together a variety of knowledge components and redirect them for the needs of households, families and consumers” (emphasis added).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation